2017
DOI: 10.2217/pgs-2017-0077
|View full text |Cite
|
Sign up to set email alerts
|

SLCO1A2, SLCO1B1 and SLCO2B1 Polymorphisms Influences Chloroquine and Primaquine Treatment in Plasmodium vivax Malaria

Abstract: The present work presents the first pharmacogenetic report of an association between chloroquine/primaquine responses with OATP transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…This study investigated the frequencies of sequence variations in eleven drug-metabolizing enzymes contributing to phase I (CYP1A2, CYP2B6, CYP2C9, CYP2C19, CYP2D6, CYP3A4 and CYP3A5) and Phase II (COMT, SULT1A1, SULT1A4 and UGT2B7) metabolism of PQ and CQ as well as seven drug transporter genes (ABCB1, ABCA1, ABCC2, ABCC4, ABCG2, SLCO1B1 and SLC25A40) in 51 Thai patients infected with P. vivax. Although the influence of drug-metabolizing enzymes and drug transporters on the efficacy of PQ treatment on P. vivax infection has been studied, 7,14,16,27 their contribution to relapse is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study investigated the frequencies of sequence variations in eleven drug-metabolizing enzymes contributing to phase I (CYP1A2, CYP2B6, CYP2C9, CYP2C19, CYP2D6, CYP3A4 and CYP3A5) and Phase II (COMT, SULT1A1, SULT1A4 and UGT2B7) metabolism of PQ and CQ as well as seven drug transporter genes (ABCB1, ABCA1, ABCC2, ABCC4, ABCG2, SLCO1B1 and SLC25A40) in 51 Thai patients infected with P. vivax. Although the influence of drug-metabolizing enzymes and drug transporters on the efficacy of PQ treatment on P. vivax infection has been studied, 7,14,16,27 their contribution to relapse is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…ABCB1 is a member of the superfamily of ATP-binding cassette (ABC) transporters like ABCG2. Sortica et al 16 reported that ABCB1 (MDR1, P-gp) T/nonG/T haplotype carriers (3435C>T, 2677G>A/ T and 1236C>T) were associated with lower parasitemia clearance rates over treatment time in a model adjusted for other clinical factors; however, there was no longer statistically significant difference after false discovery rate analysis. The absence of an association between relapse and ABCG2 in this study may be due to the small number of relapse patients and/or inhibitory effects of CQ that seems to be an inhibitor to some ABC transporters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brazilian studies of SLCO1B1 genotype in relation to drugs other than statins reported that renal transplant patients carrying the c.388G allele had lower dose adjusted blood concentration of tacrolimus compared to 388AA carriers, while SLCO1B1 c.521T>C had no effect and significant interaction between SLCO1B1 genotype and gametocytaemia clearance rate in malaria vivax patients treated with chloroquine and primaquine …”
Section: Resultsmentioning
confidence: 99%